2011
DOI: 10.3130/aijt.17.711
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Relation Between Expense and Quality of Maintenance Service for Facilities in University:

Abstract: The purpose of this study is to clarify the relation between quality and expense of cleaning service in universities. The research of expenses and specification of cleaning work order was conducted at 14 national and private universities. Results are as follows: 1) As far as cleaning expense per square meter is concerned, that of private universities is twice and more than that of national universities.2) In terms of N University, there is a big difference between cleaning service scope and frequency in each d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…A study by Tsunekawa et al (2011) investigated the quality of service in higher education institutions in Japan. Although the article was written in Japanese, information gleaned from the abstract revealed that the quality of maintenance services was a concern in universities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study by Tsunekawa et al (2011) investigated the quality of service in higher education institutions in Japan. Although the article was written in Japanese, information gleaned from the abstract revealed that the quality of maintenance services was a concern in universities.…”
Section: Literature Reviewmentioning
confidence: 99%